Formulation of Body Scrub Containing Ethanol Extract of Temulawak Rhizome (Curcuma xanthorrhiza Roxb) as a Skin Moisturizer - H, Herlina; Melda Astrika Sianipar; Yaturramadhan Harahap, Hasni; Aritonang, Barita; Yosi Darmirani (Jurnal FARMASIMED (JFM), 2025)
A body scrub is a cosmetic formulation intended to exfoliate dead skin cells and enhance skin hydration. One promising natural ingredient for body scrub formulations is the rhizome of Java turmeric (Curcuma xanthorrhiza Roxb.), which contains curcumin, a potent antioxidant known to support skin moisture retention. This study aims to evaluate the moisturizing efficacy of a body scrub formulated with Java turmeric rhizome extract. Methods: The rhizome was extracted through maceration using 96% ethanol and incorporated into body scrub formulations at concentrations of 10%, 15%, and 20%. The formulations were assessed for organoleptic characteristics, homogeneity, pH, spreadability, adhesion, oisturizing effect, and potential skin irritation on human volunteers. A commercial body scrub served as the comparator in a study involving 12 volunteers over four weeks, with applications performed once per week. Results: All Java turmeric body scrub formulations remained physically stable at room temperature and did not induce skin irritation. The physical characteristics of the formulations met standard cosmetic criteria, including consistent appearance, pH range of 6–7, spreadability between 5–7 cm, adhesion time above 4 seconds, and absence of irritation. Moisturizing effectiveness was evaluated using a skin analyzer, and data were statistically analyzed using SPSS. The p-value of 0.046 indicates that there is a significant difference between F1 and the commercial product, while for F2 and F3, there is no significant difference in moisturizing effectiveness between the temulawak formulations and the commercial product.. Among the tested formulations, the body scrub containing 20% Java turmeric extract exhibited the highest moisturizing effect. Conclusion: The body scrub formulated with Java turmeric rhizome extract, particularly at a concentration of 20%, is safe for use and shows potential as a natural moisturizing product comparable to commercial products on the market.